RENCANA STRATEGI PEMASARAN RUMAH SAKIT SAAT PANDEMI COVID-19 (STUDI KASUS RS XYZ DI BOGOR) - Dewi, Makassari (UI Scholars Hub, 2022)
The COVID-19 pandemic has changed the behavior of hospital organizations in medical services and patient behavior. This encourages the hospitals to develop specific strategies to restore patient trust by providing a sense of security for patients and customers to obtain hospital services during the COVID-19 pandemic. The purpose of this study is to formulate the design of hospital marketing strategy of XYZ Hospital Bogor during the COVID-19 pandemic. This research method is descriptive qualitative with a case study approach in the XYZ Hospital Bogor using triangulation methods. The results was XYZ Hospital Bogor developed Telemedicine and digital marketing services as a marketing strategy during the COVID-19 pandemic. The strategic design is determined based on SWOT analysis by determining strategic steps using the TOWS matrix. Besides that, this strategy design also considers STP analysis (segmenting, targeting, positioning) and the marketing mix (product, place/distribution, price, and promotion). The conclusion of this research was that XYZ Hospital Bogor more focused on digital services, especially telemedicine in health services and digital marketing as their marketing strategy.